2019
DOI: 10.1111/nyas.14174
|View full text |Cite
|
Sign up to set email alerts
|

Impact of maternal e‐cigarette vapor exposure on renal health in the offspring

Abstract: Maternal smoking during pregnancy is a significant risk factor of renal pathology in the offspring. E-cigarettes are perceived to be a safe option and are increasingly used by pregnant women either continuously during pregnancy or as a replacement for tobacco cigarettes. This study aimed to determine the effects of replacing tobacco cigarettes with e-cigarettes during pregnancy, and continuous e-cigarette use during pregnancy on the offspring's kidneys. Female Balb/c mice were exposed to either air (sham) or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
0
9

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 40 publications
1
41
0
9
Order By: Relevance
“…5 Apart from nicotine, e-vapor also contains a complex and diverse mixture of particulate matter, volatile organic compounds, and heavy metals, which can have potential health consequences when inhaled. 2 Previously, we have shown that intrauterine e-vapor exposure increased inflammatory doi: 10.1111/nyas.14411 responses in multiple organs, including the lungs, 6 brain, 7,8 and kidneys, 9 associated with mitochondrial alterations and oxidative stress (OS), 9 which are mostly nicotine-independent. However, the impacts of intrauterine e-vapor exposure on liver health and nutrient metabolism are unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Apart from nicotine, e-vapor also contains a complex and diverse mixture of particulate matter, volatile organic compounds, and heavy metals, which can have potential health consequences when inhaled. 2 Previously, we have shown that intrauterine e-vapor exposure increased inflammatory doi: 10.1111/nyas.14411 responses in multiple organs, including the lungs, 6 brain, 7,8 and kidneys, 9 associated with mitochondrial alterations and oxidative stress (OS), 9 which are mostly nicotine-independent. However, the impacts of intrauterine e-vapor exposure on liver health and nutrient metabolism are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…10 This is closely related to increased inflammation, fatty liver changes, and systemic lipid and glucose metabolic disorders in the offspring. 10,11 Given the inflammatory response and OS induced by maternal e-vapor exposure in the lungs, brain, and kidneys, [6][7][8][9] we hypothesized that long-term maternal e-vapor exposure might lead to similar disorders in the liver, resulting in glucose and lipid metabolic changes in both the dams and their offspring. Therefore, the aims of our study were to investigate the impact of maternal e-vapor exposure before gestation and during pregnancy on hepatic metabolic markers, OS, inflammation, and mitochondrial health in both the dams and their male offspring.…”
Section: Introductionmentioning
confidence: 99%
“…We have a long-standing interest in the potential health effects of e-cigarettes in children, and for example, we were the first group to show that e-cigarette use in pregnancy is likely to have detrimental effects upon the respiratory, renal and neurological health of the offspring [5][6][7][8][9]. One area of e-cigarette research where experimental data are lacking is thirdhand exposure.…”
mentioning
confidence: 99%
“…Now it is quite clear that certain flavoured e‐fluids can be toxic and e‐vaping harms not only the lung but also the other organs . Growing evidence from animal studies including those from our own group has suggested that e‐vaping during pregnancy may have detrimental impacts on multiple organ systems in the offspring at different postnatal ages, including the brain . Against the traditional beliefs, the adverse impact of maternal e‐cigarette vapour exposure on the offspring seems to be nicotine independent, suggesting noxious chemicals generated from the heated solvent may play a major role in the adverse impact on the health outcome in the offspring.…”
Section: Is Nicotine the Key Player?mentioning
confidence: 98%
“…[48][49][50] Growing evidence from animal studies including those from our own group has suggested that e-vaping during pregnancy may have detrimental impacts on multiple organ systems in the offspring at different postnatal ages, including the brain. [51][52][53][54][55] Against the traditional beliefs, the adverse impact of maternal e-cigarette vapour exposure on the offspring seems to be nicotine independent, suggesting noxious chemicals generated from the heated solvent may play a major role in the adverse impact on the health outcome in the offspring. For more detailed comparison between cigarette smoke and e-vapour exposure, please see the review by Li et al 56 Nevertheless, it can be concluded that e-cigarettes should not be used to during pregnancy.…”
Section: Is Ni Cotine the K E Y Pl Ayer?mentioning
confidence: 99%